Self Regulated dengan Resiliensi Akademik Mahasiswa - Moch. Saufi; Arifin Nur Budiono; Fakhruddin Mutakin (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2022)
The ability of an individual to survive in difficult conditions, to be able to quickly rise from adversity and be able to adapt positively to academic pressures and demands, this situation is called academic resilience. Students with high academic resilience will always be optimistic and positive in facing academic difficulties, not easily discouraged and able to get out of the problem they face. This research uses correlational quantitative method. The subjects in this study were 123 respondents consisting of 51 men and 72 women with an age range of 19-25 years. The sampling technique used is stratified random sampling. Data collection methods in this study are questionnaires and interviews. Based on the results of the rxy value is 0.413. These result indicate that the correlation coefficient is positive and is in the sufficient category. The correlation coefficient value of r=0.413 means that the contribution of the self regulated learning variable to academic resilience is 16.56% while the remaining 83.44% is from other variables. These variables or factors include students cognitive abilities, self efficacy, self esteem, student characteristics, community, environment and social support. Thus, it can be concluded that there is a relationship between self regulated learning and academic resilience of students in the 2020 academic year. Key Words : Self Regulated Learning; Academic Resilience, Student